3,3'-dichlorobiphenyl (non-Aroclor PCB-11) as a marker of non-legacy PCB contamination in marine species: comparison between Antarctic and Mediterranean bivalves - PIZZINI, Sarah; Sbicego, Chiara; CORAMI, Fabiana; Grotti, Marco; Magi, Emanuele; Bonato, Tiziano; COZZI, Giulio; BARBANTE, Carlo; PIAZZA, Rossano (Chemosphere, 2017)
In this study the accumulation of the 3,3′-dichlorobiphenyl (PCB-11) in monitoring organisms from the Antarctic and Mediterranean coastal environments has been investigated. This lesser-known PCB congener, unrelated to the industrial use of commercial mixtures, continues to be generated and released into the environment mainly as an unintentional by-product of pigment manufacturing. Specimens of the filter-feeders Adamussium colbecki from Terra Nova Bay and of Mytilus galloprovincialis and Ruditapes philippinarum from the north-western Adriatic coasts were collected and analyzed for PCB-11 by Gas Chromatography coupled both to Low-Resolution and High-Resolution Mass Spectrometry (LRMS, HRMS). In order to assess the influence of PCB-11 with respect to the legacy contamination, 126 PCB congeners related to the Aroclor commercial mixtures were simultaneously analyzed. PCB-11 was detected in all the samples, regardless of the species and of the geographical area, representing on average 17.6% and 15.6% of the total PCBs (n = 127) in Antarctic and Mediterranean samples, respectively. In the Adriatic area the highest concentrations were related to the influence of industrial activities or ship traffic, while the highest value found in Antarctic specimens, namely those collected in the austral summer 1997–1998, was ascribed to a local anthropogenic source. The occurrence of PCB-11 in the other samples from Terra Nova Bay may be related to Long-Range Atmospheric Transport (LRAT), facilitated by the higher volatility of the analyte compared to the heavier PCB congeners. Nevertheless, more in-depth studies are needed in order to evaluate the relative contribution of local and distant sources.